2012
DOI: 10.1007/bf03325796
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of using active traffic management strategies on congested freeways

Abstract: The main objective of this study is to evaluate the effectiveness of using active traffic management (ATM) strategies on freeways in terms of the driver's behavior and operational impacts. A few test beds were selected to evaluate the impacts of ATM such as speed harmonization, shoulder utilization, and ramp metering. Test beds used in this study were at places where an ATM is either proposed or previously implemented, i.e., where data exists for conditions prior to and after the implementation of ATM. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…While authors explain the calibration procedure, their own experience in demonstrating the effects of speed harmonization is strongly dependent on drivers' compliance [16] and the results cannot be compared to real-world studies (as presented in this paper). Similar results were also discussed in literature [17][18][19].…”
Section: State-of-artsupporting
confidence: 92%
“…While authors explain the calibration procedure, their own experience in demonstrating the effects of speed harmonization is strongly dependent on drivers' compliance [16] and the results cannot be compared to real-world studies (as presented in this paper). Similar results were also discussed in literature [17][18][19].…”
Section: State-of-artsupporting
confidence: 92%
“…HSR can significantly increase the capacity in frequently congested highway sections and reduce the duration of congestion period [6][7][8]. The effectiveness of HSR on highways has been evaluated in terms of drivers' behaviour and operational effects based on simulation using VISSIM [9,10], cell transmission model (CTM) [11], or DynusT [12]. The results showed that capacity increases, whereas travel time or delay time decreases after opening the shoulder lane.…”
Section: Introductionmentioning
confidence: 99%
“…mente, o stress dos motoristas. Avaliações dos impactos de implantação do gerenciamento ativo de tráfego podem ser encontradas em Mirshahi et al (2007), Carlson et al (2010), Geistefeldt (2012) e Vadde et al (2012).…”
Section: Introductionunclassified